2019
DOI: 10.1007/s40256-018-00317-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug Treatment of Hyperlipidemia in Chinese Patients: Focus on the Use of Simvastatin and Ezetimibe Alone and in Combination

Abstract: Elevated serum low-density lipoprotein cholesterol (LDL-C) is a major risk factor for coronary heart disease (CHD). Many guidelines recommend LDL-C as a primary treatment target, and statins represent the cornerstone of treatment for lipid management. Recently revised guidelines recommend even more intense management of LDL-C, especially in patients at moderate and high risk. However, LDL-C levels in the Chinese population differ from those in Western populations, and the benefits and safety of the maximum all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Patients with a clear past history of hyperlipidaemia and/or a current serum lipid test that met criteria according to the 2016 Chinese Guidelines were diagnosed with dyslipidaemia. 17 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a clear past history of hyperlipidaemia and/or a current serum lipid test that met criteria according to the 2016 Chinese Guidelines were diagnosed with dyslipidaemia. 17 …”
Section: Methodsmentioning
confidence: 99%
“…TC, TG, LDL-C, HDL-C, apolipoprotein A1 (Apo-A1) and apolipoprotein B (Apo-B) analyses were carried out using the cholesterol esterase/peroxidase enzymatic method,12 glycerophosphate oxidase/peroxidase enzymatic method,13 direct surfactant removal method,14 direct immunoinhibition method15 and immunoturbidimetry method,16 respectively, according to the manufacturers’ instructions. Patients with a clear past history of hyperlipidaemia and/or a current serum lipid test that met criteria according to the 2016 Chinese Guidelines were diagnosed with dyslipidaemia 17…”
Section: Methodsmentioning
confidence: 99%
“…Ezetimibe and simvastatin combination therapy regularly decreases LDL-C more effectively than statin monotherapies, in accordance with a number of clinical research studies findings. Additionally, the combination therapy's safety and tolerability profiles appear to be comparable to those of lowdose statin monotherapies (18). Similarly, evidence from randomized controlled studies conducted on a number of individuals revealed that adding ezetimibe to statins, as opposed to increasing the statin dose, resulted in significantly more patients meeting their LDL-C goals and much fewer patients stopping their medication due to adverse effects (19).…”
Section: Evidence From Literaturementioning
confidence: 95%
“…Twelve mice were fed a normal chow diet (NCD, #D12450B (# represents the Article Number); 10% kcal fat, 20% kcal protein, and 70% kcal carbohydrate) (NCD: corn, soybean meal, wheat bran, wheat flour, soybean oil, fish meal, calcium hydrogen phosphate, stone powder, salt, choline chloride, lysine, multiple vitamins, and mineral elements) (Xiao Shu You Tai Biotechnology Co., Ltd., Beijing, China), and twenty-four mice were fed a HFD (#D12492; 60% kcal fat, 20% kcal protein, and 20% kcal carbohydrate) (HFD: add lard, egg yolk powder, and cholesterol to NCD) to establish the diet-induced obesity (DIO) model for 18 weeks. Simvastatin (Sim) was selected as a positive drug to study the effect of ADe on blood lipids [ 31 ]. ADe fruiting body was dried and ground, and then mixed with normal saline to 80 or 160 mg/mL, and Sim mixed with normal saline to 0.6 mg/mL.…”
Section: Methodsmentioning
confidence: 99%